KAJIAN GEOLOGI BAWAH PERMUKAAN FORMASI KARANGSAMBUNG SERTA FORMASI TOTOGAN DAN HUBUNGANNYA DENGAN AKUIFER AIRTANAH DI DESA KALISANA KABUPATEN KEBUMEN - Mareta, Nandian; Ansori, Chusni (Bulletin of Scientific Contribution, 2020)
AbstractKarangsambung-Totogan Formation is the most exposed rock unit in Kalisana Village, Karangsambung, Kebumen. These two formations also form the bedrock of the study area, which consists of claystone. The Karangsambung-Totogan Formation is composed of sedimentary groups which are mixed up due to the gravity process known as Olistostrome. Pieces of centimeter to hundreds of meters of sedimentary rocks are scattered randomly during the scaly clay matrix. Kalisana Village is around 20 kilometers from the center of Kebumen Regency. Kalisana Village has an area of 349 hectares, with 109.86 hectares of rice fields and 239.14 hectares of dry land. Rice field area consists of irrigated and non-irrigated rice fields. Every year this research area often experiences water shortages during the dry season. The purpose of this study is to get a reference in making decisions to overcome the shortage of raw water in areas affected by drought through groundwater sources. The research methods include the preparation stage (literature study, previous research studies, preparation of tools, review of maps, etc.), field orientation, field work/measurements, data compilation, data analysis, evaluation and data processing. The results obtained three geological rock units namely; claystone associated with the Karangsambung Formation, a fragmented claystone unit associated with the Totogan Formation and breccias associated with the Waturanda Formation. Based on the geoelectric sonding results at three sounding locations, a subsurface image is obtained. At first sonding was found sandstones at depth of 11-18 meters with an aquifer thickness of about 7 meters. Correlation of tree geoelectric sonding location successfully described the subsurface of the Karangsambung-Totogan Formation which forms the base. The maximum geoelectric depth is around 120 meters. Keyword: Karangsambung Formation, Totogan Formation, Karangsambung, Geoelectric, aquifer AbstrakFormasi Karangsambung-Totogan merupakan satuan batuan yang paling banyak tersingkap di Desa Kalisana, Karangsambung, Kebumen. Dua formasi ini juga menjadi batuan alas di lokasi penelitian, yang terdiri dari batulempung. Formasi Karangsambung-Totogan tersusun oleh kelompok sedimen yang tercampur aduk karena proses pelongsoran gaya berat yang dikenal dengan istilah Olistostrome. Bongkah-bongkah batuan sedimen berukuran centimeter hingga ratusan meter tersebar secara acak dalam masadasar lempung hitam bersisik (scaly clay). Desa Kalisana berjarak sekitar 20 Kilometer dari pusat Kabupaten Kebumen. Desa Kalisana mempunyai luas 349 Ha, dengan luas lahan sawah 109,86 Ha dan lahan kering seluas 239,14 Ha. Luas lahan sawah terdiri dari sawah irigasi dan non-irigasi. Setiap tahun lokasi penelitian ini sering mengalami kekurangan air saat musim kemarau. Maksud penelitian ini adalah mendapatkan acuan dalam pengambilan keputusan untuk mengatasi kekurangan air baku pada daerah yang terdampak kekeringan melalui pencarian sumber airtanah. Metode penelitian meliputi tahap persiapan (studi pustaka, studi penelitian terdahulu, persiapan alat, penelaahan peta-peta, dan lain-lain), orientasi lapangan, pekerjaan lapangan/pengukuran, kompilasi data, analisis data, evaluasi dan pengolahan data. Hasil yang didapatkan berupa tiga satuan batuan geologi yaitu; batulempung yang berkorelasi dengan Formasi Karangsambung, satuan batulempung berfragmen yang berkorelasi dengan Formasi Totogan dan breksi yang termasuk Formasi Waturanda. Berdasarkan hasil geolistrik di tiga lokasi sounding didapatkan gambaran bawah permukaan. Di lokasi sonding 1 ditemukan lapisan batupasir pada kedalaman 11-18 meter dengan ketebalan akuifer sekitar 7 meter. Korelasi 3 titik sonding geolistrik berhasil menggambarkan bawah permukaan Formasi Karangsambung-Totogan yang menjadi alas tersebut. Kedalaman maksimal geolistrik sekitar 120 meter.Kata kunci: Formasi Karangsambung, Formasi Totogan, Karangsambung, Geolistrik, akuifer